Effect of physical and psychological puberty training on general well being and its dimensions in girl students - Shahrban Mehrabi; Ahmad Etemadi; Ahmad Borjali; Esmail Sadipoor (Gonabad University of Medical Sciences, 2018)
Transition through puberty is marked by an increased risk for the onset of a range of health problems, particularly those related to the control of behavior and emotion. The aim of this study was to determine the effectiveness of training puberty (physical and psychological matters) in general well being and its dimensions in girl adolescents. This was a quasi-experimental study in which the target population included all girl students at the first grade of high school in Jiroft, Iran. 40 students (20 in the experimental group and 20 in the control group) was selected using multi stage sampling method. The experimental group was educated in twelve-90- minute sessions. The content of the educational course included physical signs of puberty, physiologic change in menstrual period, hygiene, nutrition, and psychological changes of puberty. The participants completed the Skehill's general well being questionnaire before and after the intervention. Covariance analysis revealed the efficacy of education on the enhancement of psychological well being and psychological distress reduction. Therefore, it is recommended to implement health educational programs about physical and psychological matters during puberty to elementary and secondary school students to improve their mental health